The Evolution of Tau Phosphorylation and Interactions - Trushina, Nataliya I.; Bakota, Lidia; Mulkidjanian, Armen Y.; Brandt, Roland (Frontiers in Aging Neuroscience, 2019)
Tau is a neuronal microtubule-associated protein that is involved in the regulation of axonal microtubule assembly. However, as a protein with intrinsically disordered regions (IDRs), tau also interacts with many other partners in addition to microtubules. Phosphorylation at selected sites modulates tau’s various intracellular interactions and regulates the properties of IDRs. In Alzheimer’s disease and other tauopathies, tau exhibits pathologically increased phosphorylation (hyperphosphorylation) at selected sites and aggregates into neurofibrillary tangles. By bioinformatics means, we tested the hypothesis that the sequence of tau has changed during the vertebrate evolution in a way that novel interactions developed and also the phosphorylation pattern was affected, which made tau prone for the development of tauopathies. We report that distinct regions of tau show functional specialization in their molecular interactions. We found that tau’s amino-terminal region, which is involved in biological processes related to “membrane organization” and “regulation of apoptosis”, exhibited a strong evolutionary increase in protein disorder providing the basis for the development of novel interactions. We observed that the predicted phosphorylation sites have changed during evolution in a region-specific manner, and in some cases the overall number of phosphorylation sites increased owing to formation of clusters of phosphorylatable residues. In contrast, disease-specific hyperphosphorylated sites remained highly conserved. The data indicate that novel, non-microtubule related tau interactions developed during evolution and suggest that the biological processes, which are mediated by these interactions, are of pathological relevance. Furthermore, the data indicate that predicted phosphorylation sites in some regions of tau, including a cluster of phosphorylatable residues in the alternatively spliced exon 2, have changed during evolution. In view of the “antagonistic pleiotropy hypothesis” it may be worth to take disease-associated phosphosites with low evolutionary conservation as relevant biomarkers into consideration.